A sulfide all-solid-state battery and a preparation method therefor, and an electric device
Patent Information
- Application Number
- CN202611338068.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-31
- Publication Date
- 2026-10-30
AI Technical Summary
[0002]随着电动汽车和便携式电子设备的快速发展,对锂离子电池的能量密度与安全性要求的不断提高,锂离子电池体系正在从液态向全固态电池转变,全固态电池中,硫化物固态电解质因具有较高的室温离子电导率而成为国内主流技术路线,但其自身存在化学稳定性差、工业化制造成本高的问题,并且与正极、负极材料之间的界面不稳定性始终是技术瓶颈
[0016]与现有技术相比,本申请的有益效果包括:
Smart Images

Figure CN123018085A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of solid-state battery technology, and in particular to a sulfide all-solid-state battery, its preparation method, and an electrical device thereof. Background Technology
[0002] With the rapid development of electric vehicles and portable electronic devices, and the increasing demands for energy density and safety of lithium-ion batteries, lithium-ion battery systems are shifting from liquid to all-solid-state batteries. Among all-solid-state batteries, sulfide solid electrolytes have become the mainstream technology in China due to their high room-temperature ionic conductivity. However, they suffer from poor chemical stability and high industrial manufacturing costs, and the interfacial instability between them and the cathode and anode materials remains a technological bottleneck. Regarding cathode materials, the commonly used lithium cobalt oxide, lithium iron phosphate, and ternary cathode materials in traditional liquid systems still face significant shortcomings in solid-state systems: lithium cobalt oxide and ternary materials contain large amounts of precious metals such as cobalt and nickel, leading to high costs; the actual specific capacity of lithium cobalt oxide and lithium iron phosphate is relatively low, making it difficult to meet high energy density requirements; all three types of oxide cathodes exhibit lattice oxygen release reactions during cycling, posing thermal safety hazards, with the ternary cathode showing the most prominent risk. Furthermore, interfacial side reactions easily occur between ternary cathodes and lithium iron phosphate and sulfide solid electrolytes. To match sulfide solid electrolytes, sulfur-based cathodes, which use sulfur or lithium sulfide as active materials and are oxygen-free, directly avoid the oxygen release problem. They also achieve high theoretical specific capacity and energy density based on multi-electron conversion reactions. Furthermore, in a solid system, they can avoid the shuttle effect caused by polysulfide dissolution in liquid lithium-sulfur batteries.
[0003] However, sulfur-based cathodes still suffer from the following drawbacks in solid-state batteries: their intrinsic electronic and ionic conductivity is low, limiting lithium-ion diffusion and electron transport; significant volume changes occur during lithium insertion / extraction, easily disrupting the solid-solid interface contact; and the interfacial compatibility between sulfur-based cathodes and sulfide solid electrolytes is insufficient, resulting in high interfacial impedance. On the anode side, the actual specific capacity of traditional graphite anodes is approaching the theoretical limit, failing to meet the high energy density requirements of solid-state batteries; lithium metal anodes, on the other hand, have not yet been put into practical use due to safety issues caused by uncontrolled lithium dendrite growth. Silicon-based anodes are considered the next generation of anode materials due to their extremely high theoretical specific capacity, abundant crustal reserves, and low operating potential. However, they still face the following problems in sulfide solid-state battery systems: Silicon is a semiconductor with low intrinsic ionic and electronic conductivity, which restricts the diffusion of lithium ions and the rapid transport of electrons inside the anode; continuous interfacial side reactions occur when silicon comes into contact with sulfide electrolytes, generating an insulating interfacial layer that hinders lithium ion transport and causes continuous loss of active lithium; silicon expands by more than 300% during charging and discharging, and the drastic volume change leads to cracking of silicon particles, solid-solid interface separation, and detachment of active materials from the current collector.
[0004] The multiple defects in the aforementioned positive and negative electrodes, as well as their interfaces with the sulfide solid electrolyte, are coupled together, causing the cycle performance of all-solid-state batteries with sulfur-based positive and silicon-based negative electrodes to degrade rapidly, making it difficult to meet the requirements of practical applications. Therefore, there is an urgent need for an all-solid-state battery technology that can simultaneously improve the conductivity of sulfur-based positive and silicon-based negative electrodes, effectively suppress volumetric strain, and stabilize the interface between both and the sulfide solid electrolyte. Summary of the Invention
[0005] The purpose of this application is to provide a sulfide all-solid-state battery, its preparation method, and an electrical device thereof, in order to solve the above-mentioned problems.
[0006] To achieve the above objectives, this application adopts the following technical solution: The first aspect of this application provides a sulfide all-solid-state battery, comprising a sulfur-based composite positive electrode active material, a silicon-based composite negative electrode active material, and a solid electrolyte; the sulfur-based composite positive electrode active material comprises a sulfur-based active material, a positive electrode conductive agent, and a positive electrode electrolyte; the silicon-based composite negative electrode active material comprises a silicon-based active material, a negative electrode conductive agent, and a negative electrode electrolyte; The sulfur-based active material includes one or more of lithium sulfide, lithium iron sulfide, and lithium titanium sulfide. The positive electrode electrolyte includes Li 10 GeP2S 12 One or more of Li6PS5X, Li3PS4, and aLi2S·(100-a)P2S5 Where X = Cl, Br or I, 0 < a < 100.
[0007] Optionally, the silicon-based active material includes one or more of silicon, β-SiC-coated spherical silicon-carbon materials, and β-SiC-coated non-spherical silicon-carbon materials.
[0008] Optionally, the mass ratio of the positive electrode electrolyte, the positive electrode conductive agent, and the sulfur-based active material is (40~60):(10~30):(10~30); And / or, The mass ratio of the negative electrode electrolyte, the negative electrode conductive agent and the silicon-based active material is (50~10):(30~5):(80~50).
[0009] Optionally, the median particle size D of the positive electrode electrolyte 50 The range is 0.5~10µm; And / or, The median particle size D of the negative electrode electrolyte 50 The value is 0.5~10µm.
[0010] Optionally, the sulfide all-solid-state battery satisfies at least one of the following conditions: (1) The positive electrode conductive agent includes one or more of Ketjen black, acetylene black, conductive carbon black, and vapor-grown carbon fiber; (2) The negative electrode conductive agent includes one or more of Ketjen black, acetylene black, conductive carbon black, and vapor-grown carbon fiber; (3) The negative electrode electrolyte includes Li 10 GeP2S 12 One or more of Li6PS5X, Li3PS4, and aLi2S·(100-a)P2S5 Where X = Cl, Br or I, 0 < a < 100; (4) The solid electrolyte includes Li 10 GeP2S 12 One or more of Li6PS5X, Li3PS4, and aLi2S·(100-a)P2S5 Where X = Cl, Br or I, 0 < a < 100.
[0011] A second aspect of this application provides a method for preparing the above-mentioned sulfide all-solid-state battery, comprising: Sulfur-based active material, positive electrode electrolyte and positive electrode conductive agent were ball-milled to obtain sulfur-based composite positive electrode active material; A silicon-based active material, a negative electrode conductive agent, and a negative electrode electrolyte are mixed to obtain a silicon-based composite negative electrode active material. A sulfide all-solid-state battery was prepared using the sulfur-based composite positive electrode active material, the silicon-based composite negative electrode active material, and the solid electrolyte.
[0012] Optionally, the ball milling conditions include: ball milling using ball milling media under a protective atmosphere.
[0013] Optionally, the preparation method satisfies at least one of the following conditions: The ball-to-material ratio of the ball mill is 1:1 to 30:1; The milling media include one or both of zirconia balls and agate balls; The diameter of the ball milling media is 2~20mm; The rotational speed of the ball mill is 400~1000 r / min; The ball milling time is 0.5 to 10 hours.
[0014] Optionally, the mixing method of the silicon-based active material, the negative electrode conductive agent and the negative electrode electrolyte includes one or more of hand grinding, ball milling and wet mixing.
[0015] A third aspect of this application provides an electrical device comprising the aforementioned sulfide all-solid-state battery, or a sulfide all-solid-state battery prepared by the aforementioned preparation method.
[0016] Compared with the prior art, the beneficial effects of this application include: This application provides a sulfide-based all-solid-state battery, comprising a sulfide-based composite positive electrode active material, a silicon-based composite negative electrode active material, and a solid electrolyte. The sulfide-based composite positive electrode active material includes a sulfide-based active material, a positive electrode conductive agent, and a positive electrode electrolyte. This application prepares a sulfide-based composite positive electrode active material and a silicon-based composite negative electrode active material with good interfacial compatibility with the sulfide solid electrolyte, and matches them with a sulfide solid electrolyte to form a sulfide-based all-solid-state battery, exhibiting extremely high specific capacity and stable cycle performance. On the positive electrode side, utilizing the special reaction mechanism between the sulfide-based active material and the positive electrode electrolyte, the low ionic conductivity problem of the positive electrode material is solved while achieving "self-lithiation," continuously replenishing the active material lost during battery cycling, thus achieving a stable increase in battery capacity and stable cycling performance. Meanwhile, when the sulfide all-solid-state battery is cycling, the volume changes of the sulfur-based composite positive electrode active material and the silicon-based composite negative electrode active material compensate each other during the process of positive electrode delithiation shrinkage-negative electrode lithium insertion expansion / positive electrode lithium insertion expansion-negative electrode delithiation shrinkage, thereby greatly reducing the pressure requirements for battery operation. At the same time, each material system has high safety and theoretically avoids the risk of thermal runaway, which has broad research space and application prospects.
[0017] The method for preparing the above-mentioned sulfide all-solid-state battery provided in this application involves preparing a sulfide-based composite positive electrode active material in one step through high-energy ball milling. During the preparation process, the sulfide-based active material reacts with the positive electrode electrolyte to generate a high-ionic-conductivity intermediate phase. The electrolyte partially decomposes to obtain lithium sulfide products. The lithium sulfide products continuously activate and replenish the active material and active lithium source in subsequent reactions, enabling the battery to "self-replenish lithium" and improve battery capacity and cycle stability. In addition, this application reduces the expansion of the silicon-based composite negative electrode by spheroidizing, realizing a benign three-phase interface of silicon-based negative electrode-sulfide solid electrolyte-sulfide positive electrode. Furthermore, the volume expansion characteristics of the sulfide-based composite positive electrode active material and the silicon-based composite negative electrode active material are used to achieve pressure compensation, reducing the battery operating pressure.
[0018] The electrical device provided in this application includes a sulfide all-solid-state battery. Relying on oxygen-free sulfur-based composite positive electrode active material, high-specific-capacity silicon-based composite negative electrode active material, and interface optimization of positive and negative electrode materials for sulfide solid electrolyte, it exhibits extremely high capacity and cycle performance, as well as extremely low operating pressure. It is of great significance for the implementation of all-solid-state battery technology with high safety, high energy density, and low operating pressure. Attached Figure Description
[0019] To more clearly illustrate the technical solutions of the embodiments of this application, the accompanying drawings used in the embodiments will be briefly described below. It should be understood that the following drawings only show some embodiments of this application and should not be regarded as a limitation on the scope of this application.
[0020] Figure 1 A physical image of the sulfur-based composite positive electrode active material provided in Example 1; Figure 2 The sulfide all-solid-state battery mold provided in Example 1; Figure 3 The first charge-discharge curve for the half-cell test provided in Example 1; Figure 4 The first charge-discharge curve for the sulfide all-solid-state battery provided in Example 13; Figure 5 Cycling curves for testing the sulfide all-solid-state battery provided in Example 13. Detailed Implementation
[0021] As used in this article: "Prepared from" is synonymous with "comprising". The terms "comprising", "including", "having", "containing", or any other variations thereof as used herein are intended to cover non-exclusive inclusion. For example, a composition, step, method, article, or apparatus that includes the listed elements is not necessarily limited to those elements, but may include other elements not expressly listed or elements inherent to such composition, step, method, article, or apparatus.
[0022] The conjunction "composed of..." excludes any unspecified elements, steps, or components. If used in a claim, this phrase makes the claim closed, excluding materials other than those described, except for associated conventional impurities. When the phrase "composed of..." appears in a clause of the body of a claim rather than immediately following it, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0023] When a quantity, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pair of any upper or preferred value with any lower or preferred value, regardless of whether the range is disclosed individually. For example, when the range “1–5” is disclosed, the described range should be interpreted as including ranges “1–4”, “1–3”, “1–2”, “1–2 and 4–5”, “1–3 and 5”, etc. When numerical ranges are described herein, unless otherwise stated, the range is intended to include its endpoints and all integers and fractions within that range.
[0024] In these embodiments, unless otherwise specified, the portions and percentages are all by weight.
[0025] "Parts by mass" refers to the basic unit of measurement that expresses the mass ratio of multiple components. One part can represent any unit mass, such as 1g or 2.689g. If we say that component A has "a" parts by mass and component B has "b" parts by mass, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it can mean that the mass of component A is aK and the mass of component B is bK (where K is any number representing a multiplier). It is important to understand that, unlike parts by mass, the sum of the mass parts of all components is not limited to 100 parts.
[0026] "And / or" is used to indicate that one or both of the described situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0027] To better illustrate the technical solution provided in this application, the technical solution will be described in its entirety before the embodiments, as follows: In a first aspect, this application provides a sulfide all-solid-state battery, comprising a sulfur-based composite positive electrode active material, a silicon-based composite negative electrode active material, and a solid electrolyte; the sulfur-based composite positive electrode active material comprises a sulfur-based active material, a positive electrode conductive agent, and a positive electrode electrolyte; the silicon-based composite negative electrode active material comprises a silicon-based active material, a negative electrode conductive agent, and a negative electrode electrolyte. The sulfur-based active materials include lithium sulfide (Li2S), lithium iron sulfide (Li2FeS2), and lithium titanium sulfide (Li... 1.2 Ti 0.8 One or more of S2); The positive electrode electrolyte includes Li 10 GeP2S 12 One or more of Li6PS5X, Li3PS4, and aLi2S·(100-a)P2S5 Where X = Cl, Br or I, 0 < a < 100.
[0028] In one optional embodiment, the silicon-based active material includes one or more of silicon, β-SiC-coated spherical silicon-carbon materials, and β-SiC-coated non-spherical silicon-carbon materials.
[0029] In one optional embodiment, the silicon-based active material includes one or both of β-SiC-coated spherical silicon-carbon materials and β-SiC-coated non-spherical silicon-carbon materials.
[0030] In one optional embodiment, the mass ratio of the positive electrode electrolyte, the positive electrode conductive agent, and the sulfur-based active material is (40~60):(10~30):(10~30); And / or, The mass ratio of the negative electrode electrolyte, the negative electrode conductive agent and the silicon-based active material is (50~10):(30~5):(80~50).
[0031] Optionally, the mass ratio of the positive electrode electrolyte, the positive electrode conductive agent, and the sulfur-based active material can be any ratio between 40:10:10, 45:15:15, 50:20:20, 55:25:25, 60:30:30, or (40~60):(10~30):(10~30). The mass ratio of the negative electrode electrolyte, the negative electrode conductive agent, and the silicon-based active material can be any ratio between 50:30:80, 40:20:70, 30:15:60, 20:10:55, 10:5:50, or (50~10):(30~5):(80~50).
[0032] In an optional embodiment, the median particle size D of the positive electrode electrolyte 50 The range is 0.5~10µm; And / or, The median particle size D of the negative electrode electrolyte 50 The value is 0.5~10µm.
[0033] Optionally, the median particle size D of the positive electrode electrolyte 50 It can be 0.5µm, 1µm, 5µm, 10µm, or any value between 0.5 and 10µm; The median particle size D of the negative electrode electrolyte 50 It can be 0.5µm, 1µm, 5µm, 10µm, or any value between 0.5 and 10µm.
[0034] In an optional embodiment, the sulfide all-solid-state battery satisfies at least one of the following conditions: (1) The positive electrode conductive agent includes one or more of Ketjen black, acetylene black, conductive carbon black, and vapor-grown carbon fiber; (2) The negative electrode conductive agent includes one or more of Ketjen black, acetylene black, conductive carbon black, and vapor-grown carbon fiber; (3) The negative electrode electrolyte includes Li 10 GeP2S 12 One or more of Li6PS5X, Li3PS4, and aLi2S·(100-a)P2S5 Where X = Cl, Br or I, 0 < a < 100; (4) The solid electrolyte includes Li 10 GeP2S 12 One or more of Li6PS5X, Li3PS4, and aLi2S·(100-a)P2S5 Where X = Cl, Br or I, 0 < a < 100.
[0035] It should be noted that the negative electrode electrolyte is used to construct the ion transport network in the composite negative electrode, while the negative electrode conductive agent is used to construct the electron transport network in the composite negative electrode.
[0036] Secondly, this application provides a method for preparing the above-mentioned sulfide all-solid-state battery, comprising: Sulfur-based active material, positive electrode electrolyte and positive electrode conductive agent were ball-milled to obtain sulfur-based composite positive electrode active material; A silicon-based active material, a negative electrode conductive agent, and a negative electrode electrolyte are mixed to obtain a silicon-based composite negative electrode active material. A sulfide all-solid-state battery was prepared using the sulfur-based composite positive electrode active material, the silicon-based composite negative electrode active material, and the solid electrolyte.
[0037] In an optional embodiment, the ball milling conditions include: ball milling using ball milling media under a protective atmosphere.
[0038] In an optional embodiment, the preparation method satisfies at least one of the following conditions: The ball-to-material ratio of the ball mill is 1:1 to 30:1; The milling media include one or both of zirconia balls and agate balls; The diameter of the ball milling media is 2~20mm; The rotational speed of the ball mill is 400~1000 r / min; The ball milling time is 0.5 to 10 hours.
[0039] Optionally, the ball-to-material ratio of the ball mill can be 1:1, 10:1, 20:1, 30:1, or any ratio between 1:1 and 30:1; The diameter of the ball milling media can be 2mm, 5mm, 10mm, 20mm, or any value between 2 and 20mm; The rotational speed of the ball mill can be 400 r / min, 600 r / min, 800 r / min, 1000 r / min, or any value between 400 and 1000 r / min; The ball milling time can be 0.5h, 2h, 5h, 10h, or any value between 0.5h and 10h.
[0040] In one optional embodiment, the mixing method of the silicon-based active material, the negative electrode conductive agent, and the negative electrode electrolyte includes one or more of hand grinding, ball milling, and wet mixing.
[0041] Thirdly, this application provides an electrical device including the above-mentioned sulfide all-solid-state battery, or a sulfide all-solid-state battery prepared by the above-mentioned preparation method.
[0042] The implementation schemes of this application will be described in detail below with reference to specific embodiments. However, those skilled in the art will understand that the following embodiments are only for illustrating this application and should not be regarded as limiting the scope of this application. Unless otherwise specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments used without specified manufacturers are all conventional products that can be purchased commercially.
[0043] Material sources for the examples and comparative examples: Vapor-grown carbon fiber (VGCF): KELUDE (MA-EN-CO-0009).
[0044] Example 1 This embodiment provides a sulfide all-solid-state battery and its preparation method. The specific preparation steps are as follows: Preparation of sulfur-based composite positive electrode active materials: Take 1g of lithium sulfide (25%), and the electrolyte Li6PS5Cl (D 50 2g of 1.2µm (50%) and 1g of vapor-grown carbon fiber (VGCF) (25%) were ball-milled under the following conditions: a planetary ball mill, a zirconia grinding jar, and zirconia balls with a diameter of 8mm, a ball-to-material ratio of 15:1, a rotation speed of 400rpm, and ball milling under an argon atmosphere for 0.5h to obtain a sulfur-based composite positive electrode active material. Figure 1 As shown.
[0045] Preparation of silicon-based composite anode active materials: Take 60 mg of pure silicon (60% of the total volume), and the electrolyte Li6PS5Cl (D... 50 The silicon-based composite anode active material was prepared by manually grinding 30 mg of 1.2µm carbon fiber (30% of the total content) and 10 mg of vapor-grown carbon fiber (10% of the total content).
[0046] Preparation of sulfide all-solid-state batteries: In an argon-protected glove box, 85 mg of sulfide electrolyte Li6PS5Cl (D) was loaded into a 10 mm diameter solid-state battery mold. 50 The electrolyte layer was pressed under an external pressure of 2.5T (3.5µm), and 2.6mg of sulfur-based composite positive electrode active material was loaded. The composite positive electrode layer was pressed under an external pressure of 2.5T for 5min. On the opposite side, an indium sheet with a thickness of 100µm and a diameter of 10mm and an 8mm lithium sheet were sequentially filled to complete the assembly of the positive electrode half cell. In an argon-protected glove box, 85 mg of sulfide electrolyte Li6PS5Cl (D) was placed in a 10 mm diameter solid-state battery mold. 50 The electrolyte layer was pressed under an applied pressure of 2.5T (3.5µm), followed by the loading of 1.38mg of silicon-based composite negative electrode active material. The composite negative electrode layer was then pressed under an applied pressure of 5T for 5 minutes. Next, 5.2mg of sulfur-based composite positive electrode active material was loaded, and the sulfide all-solid-state battery was assembled under an applied pressure of 2.5T for 5 minutes. The sulfide all-solid-state battery mold is shown below. Figure 2 As shown.
[0047] Example 2-18 Most of the preparation steps in Examples 2-18 are the same as those in Example 1, with the differences shown in Table 1.
[0048] Table 1. Fabrication parameters of sulfide all-solid-state batteries in the examples and comparative examples.
[0049] Example 19 This embodiment provides a sulfide all-solid-state battery and its preparation method. The specific preparation steps are as follows: Preparation of sulfur-based composite positive electrode active materials: Take 1g of lithium sulfide (25%), and the electrolyte Li6PS5Cl (D 50 2g of 1.2µm (50%) and 1g of acetylene black (25%) were ball-milled. The ball-milling conditions were as follows: a planetary ball mill, a zirconia ball milling jar and zirconia balls with a diameter of 8mm, a ball-to-material ratio of 30:1, a rotation speed of 500rpm, and ball milling for 1h under an argon atmosphere to obtain a sulfur-based composite positive electrode active material.
[0050] Preparation of silicon-based composite anode active materials: Take 60 mg of β-SiC-coated spherical silicon-carbon material (60% of the total content), and the electrolyte Li6PS5Cl (D 50 The silicon-based composite anode active material was prepared by manually grinding 30 mg of 1.2µm carbon fiber (30%) and 10 mg of vapor-grown carbon fiber (10%).
[0051] Preparation of sulfide all-solid-state batteries: In an argon-protected glove box, 85 mg of sulfide electrolyte Li6PS5Cl (D) was loaded into a 10 mm diameter solid-state battery mold. 50 The electrolyte layer was pressed under an external pressure of 2.5T (3.5µm), and 2.6mg of sulfur-based composite positive electrode active material was loaded. The composite positive electrode layer was pressed under an external pressure of 2.5T for 5min. On the opposite side, an indium sheet with a thickness of 100µm and a diameter of 10mm and an 8mm lithium sheet were sequentially filled to complete the assembly of the positive electrode half cell. In an argon-protected glove box, 85 mg of sulfide electrolyte Li6PS5Cl (D) was placed in a 10 mm diameter solid-state battery mold. 50 The electrolyte layer was pressed under an applied pressure of 2.5T (3.5µm), 1.72mg of silicon-based composite negative electrode active material was loaded, and the composite negative electrode layer was pressed under an applied pressure of 5T for 5min. Then, 5.2mg of sulfur-based composite positive electrode active material was loaded, and the sulfide all-solid-state battery was assembled under an applied pressure of 2.5T for 5min.
[0052] Comparative Example 1 The difference from Example 1 is that manual grinding was used instead of ball milling when preparing the sulfur-based composite positive electrode active material, while the rest of the preparation steps were the same as in Example 1.
[0053] Comparative Example 2 The difference from Example 1 is that the sulfur-based active material is first mixed with the positive electrode electrolyte, manually ground, and then ball-milled with the positive electrode conductive agent. The remaining preparation steps are the same as in Example 1.
[0054] Comparative Example 3 The difference from Example 13 is that manual grinding was used instead of ball milling when preparing the sulfur-based composite positive electrode active material, while the rest of the preparation steps were the same as in Example 13.
[0055] Comparative Example 4 The difference from Example 13 is that the sulfur-based active material is first mixed with the positive electrode electrolyte, manually ground, and then ball-milled with the positive electrode conductive agent. The remaining preparation steps are the same as in Example 13.
[0056] Comparative Example 5 The difference from Example 1 is that the positive electrode electrolyte (Li6PS5Cl) is replaced with Li2ZrCl6, while the rest of the preparation steps are the same as in Example 1.
[0057] The electrochemical performance of the assembled half-cell and sulfide all-solid-state battery was tested, and the test results are shown in Table 2.
[0058] Table 2 Electrochemical performance test results of the examples and comparative examples
[0059] Based on the above test results, Example 1, which uses a one-step ball milling method to prepare sulfur-based composite positive electrode active material, achieved a first discharge capacity of 1345.83 mAh / g for the half-cell and 527.57 mAh / g for the full-cell. Both the half-cell and full-cell showed a capacity retention of >100% after 100 cycles, and the operating pressure was 75 MPa. These results demonstrate that ball milling the sulfur-based active material, positive electrode electrolyte, and positive electrode conductive agent together effectively initiated an in-situ reaction, achieving "self-lithiation" while providing high capacity. Figure 3 As shown, the initial discharge capacity of the positive electrode half-cell is higher than the charging capacity, indicating that the electrolyte reaction contributes to the capacity.
[0060] Examples 2-19 used different sulfur-based active materials (Li2S, Li2FeS2, Li 1.2 Ti 0.8 S2), silicon-based active materials (pure silicon, β-SiC-coated spherical silicon-carbon, β-SiC-coated non-spherical silicon-carbon), and electrolytes (Li6PS5Cl, Li3PS4, Li 10 GeP2S 12 The method used was to co-mill the sulfur-based active material, positive electrode electrolyte, and positive electrode conductive agent in one step. The resulting battery exhibited extremely high initial discharge capacity in both half-cell and full-cell configurations, and the capacity retention rate after 100 cycles exceeded or approached 100%, successfully achieving "self-lithiation" and obtaining extremely high capacity and stable cycle performance. On the other hand, Example 19 used a different positive electrode conductive agent than Examples 1-18, confirming that the type of conductive agent affects the capacity utilization of the positive electrode material after "self-lithiation," but the "self-lithiation" phenomenon still occurred. Figure 4 and Figure 5 As shown, after the first reaction in Example 13, the full battery capacity continuously increased, indicating that the products of the electrolyte reaction participated in the charge and discharge in subsequent cycles, replenishing the loss of active materials and active lithium sources in the positive electrode, so that the battery cycle retention rate was higher than 100% after 100 cycles. It should be noted that the first discharge capacity of the full battery is much lower than the half-cell reversible capacity. This is because the surface load of the composite positive electrode in the full battery is much higher than that in the half-cell. Under the high surface load, the capacity of the lithium sulfide composite positive electrode is affected to a certain extent.
[0061] Comparative Examples 1 and 3, using only manual grinding, failed to achieve an effective reaction between the sulfur-based active material and the positive electrode electrolyte, resulting in almost no capacity utilization. Comparative Examples 2 and 4 employed a stepwise method of first manually grinding the sulfur-based active material and the positive electrode electrolyte, followed by ball milling with the addition of a positive electrode conductive agent. While this resulted in a slight capacity increase, an effective "self-lithiation" mechanism could not be established, leading to unstable cycle performance. This demonstrates that only through a single-step ball milling process can the interfacial reaction between the sulfur-based active material and the positive electrode electrolyte be fully established, achieving high capacity and self-lithiation. Comparative Example 5, using Li₂ZrCl₆ (not specified in this application) to replace the positive electrode electrolyte, exhibited an initial discharge capacity of only 10.87 mAh / g, proving that the type of positive electrode electrolyte specified in this application is a necessary condition for achieving an effective "self-lithiation" mechanism in sulfide-based all-solid-state batteries.
[0062] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.
Claims
1. A sulfide all-solid-state battery, characterized in that, The invention includes a sulfur-based composite positive electrode active material, a silicon-based composite negative electrode active material, and a solid electrolyte; the sulfur-based composite positive electrode active material includes a sulfur-based active substance, a positive electrode conductive agent, and a positive electrode electrolyte; the silicon-based composite negative electrode active material includes a silicon-based active substance, a negative electrode conductive agent, and a negative electrode electrolyte. The sulfur-based active material includes one or more of lithium sulfide, lithium iron sulfide, and lithium titanium sulfide. The positive electrode electrolyte includes Li 10 GeP2S 12 One or more of Li6PS5X, Li3PS4, and aLi2S·(100-a)P2S5 Where X = Cl, Br or I, 0 < a < 100.
2. The sulfide all-solid-state battery according to claim 1, characterized in that, The silicon-based active material includes one or more of silicon, β-SiC-coated spherical silicon-carbon materials, and β-SiC-coated non-spherical silicon-carbon materials.
3. The sulfide all-solid-state battery according to claim 1, characterized in that, The mass ratio of the positive electrode electrolyte, the positive electrode conductive agent and the sulfur-based active material is (40~60):(10~30):(10~30); And / or, The mass ratio of the negative electrode electrolyte, the negative electrode conductive agent and the silicon-based active material is (50~10):(30~5):(80~50).
4. The sulfide all-solid-state battery according to claim 1, characterized in that, The median particle size D of the positive electrode electrolyte 50 The range is 0.5~10µm; And / or, The median particle size D of the negative electrode electrolyte 50 The value is 0.5~10µm.
5. The sulfide all-solid-state battery according to claim 1, characterized in that, At least one of the following conditions must be met: (1) The positive electrode conductive agent includes one or more of Ketjen black, acetylene black, conductive carbon black, and vapor-grown carbon fiber; (2) The negative electrode conductive agent includes one or more of Ketjen black, acetylene black, conductive carbon black, and vapor-grown carbon fiber; (3) The negative electrode electrolyte includes Li 10 GeP2S 12 One or more of Li6PS5X, Li3PS4, and aLi2S·(100-a)P2S5 Where X = Cl, Br or I, 0 < a < 100; (4) The solid electrolyte includes Li 10 GeP2S 12 One or more of Li6PS5X, Li3PS4, and aLi2S·(100-a)P2S5 Where X = Cl, Br or I, 0 < a < 100.
6. A method for preparing a sulfide all-solid-state battery as described in any one of claims 1-5, characterized in that, include: Sulfur-based active material, positive electrode electrolyte and positive electrode conductive agent were ball-milled to obtain sulfur-based composite positive electrode active material; A silicon-based active material, a negative electrode conductive agent, and a negative electrode electrolyte are mixed to obtain a silicon-based composite negative electrode active material. A sulfide all-solid-state battery was prepared using the sulfur-based composite positive electrode active material, the silicon-based composite negative electrode active material, and the solid electrolyte.
7. The preparation method according to claim 6, characterized in that, The conditions for ball milling include: ball milling using ball milling media under a protective atmosphere.
8. The preparation method according to claim 7, characterized in that, At least one of the following conditions must be met: The ball-to-material ratio of the ball mill is 1:1 to 30:1; The milling media include one or both of zirconia balls and agate balls; The diameter of the ball milling media is 2~20mm; The rotational speed of the ball mill is 400~1000 r / min; The ball milling time is 0.5 to 10 hours.
9. The preparation method according to claim 6, characterized in that, The mixing method of the silicon-based active material, the negative electrode conductive agent and the negative electrode electrolyte includes one or more of the following: manual grinding, ball milling and wet mixing.
10. An electrical appliance, characterized in that, This includes the sulfide all-solid-state battery according to any one of claims 1-5, or the sulfide all-solid-state battery prepared by the preparation method according to any one of claims 6-9.